A crown of ivy and glass - Legrand, Claire, 1986- (Legrand, Claire, 1986- Middlemist trilogy, 2023)
"Lady Gemma Ashbourne seemingly has it all. She's young, gorgeous, and rich. Her family was Anointed by the gods, blessed with incredible abilities. But underneath her glittering façade, Gemma is deeply sad. Years ago, her sister Mara was taken to the Middlemist to guard against treacherous magic. Her mother abandoned the family. Her father and eldest sister, Farrin--embroiled in a deadly blood feud with the mysterious Bask family--often forget Gemma exists. Worst of all, Gemma is the only Ashbourne to possess no magic. Instead, her body fights it like poison. Constantly ill, aching with loneliness, Gemma craves love and yearns to belong. Then she meets the devastatingly handsome Talan d'Astier. His family destroyed themselves, seduced by a demon, and Talan, the only survivor, is determined to redeem their honor. Intrigued and enchanted, Gemma proposes a bargain: She'll help Talan navigate high society if he helps her destroy the Basks. According to popular legend, a demon called The Man With the Three-Eyed Crown is behind the families' blood feud--slay the demon, end the feud. But attacks on the Middlemist are increasing. The plot against the Basks quickly spirals out of control. And something immense and terrifying is awakening in Gemma, drawing her inexorably toward Talan and an all-consuming passion that could destroy her--or show her the true strength of her power at last." --